(untitled) (Journal of the College of Education for Women, 2023)
The study aimed to identify the degree of availability of design Thinking Indicators in The content of the Arabic Language Curricula at the secondary stage in the Syrian Arab Republic; to achieve the goal of the study. The researcher used the Descriptive Approach based on the analysis method according to the Cognitive Theory. The study tools consist of a list of Design Thinking Indicators and a Content Analysis Tool. The researcher completed the Validity and Reliability procedures for the tools. After applying them, the results of the study resulted in the following: Greater Interest than other sub-skills. The results also showed a Divergence of care for the sub-skills and the Difference in their recurrence rate, and the Omission of some sub-skills that did not have any opportunity to be trained on, sub-indicators of Design Thinking.